2009
DOI: 10.1007/s12253-009-9229-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid Cyst in an Intrapancreatic Accessory Spleen: Three Case Reports and Review of the Literatures

Abstract: The development of an epidermoid cyst in an intrapancreatic accessory spleen is an extremely rare lesion, with only 17 cases being reported in the English literature. All such cases were located in the pancreatic tail, some of which showed carbohydrate antigen 19-9 (CA19-9) immunoreactivity in the lining of the epithelium. A few of them indicated an elevation of the serum CA19-9 level. Here we report three cases of an epidermoid cyst in an intrapancreatic accessory spleen. Cases 1 and 2 were 57-year-old and 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…However, the exact incidence of ECIPAS is difficult to determine as over 50% of the cases were incidentally detected [8,9,12,14,15,18,19,22-24], [26,27,30,32,34]. The mean age of the patients was 46.1 years (range 12 to 70 years), with a female preponderance (58.3%) [6,7,10-13,16,17,19-21,24-26,28], [31,33,34,36]. It is noteworthy that the majority of patients were of Asian origin (28/36 patients, 77.7%), suggesting possibly the presence of a racial factor [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact incidence of ECIPAS is difficult to determine as over 50% of the cases were incidentally detected [8,9,12,14,15,18,19,22-24], [26,27,30,32,34]. The mean age of the patients was 46.1 years (range 12 to 70 years), with a female preponderance (58.3%) [6,7,10-13,16,17,19-21,24-26,28], [31,33,34,36]. It is noteworthy that the majority of patients were of Asian origin (28/36 patients, 77.7%), suggesting possibly the presence of a racial factor [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the splenic epithelial cyst, the origin of which was difficult to identify preoperatively, was associated with exacerbation of symptoms, elevated serum CA19-9 levels, and an increased size after 6 years of follow-up. Concerning the preoperative diagnosis of the current case, an epithelial cyst (10), including epidermoid (8) or lymphoepithelial (9, 11) cysts, was strongly suspected due to the extremely high level of serum CA19-9 (2,5,8,9).…”
Section: Discussionmentioning
confidence: 92%
“…Epithelial cysts are not specific to the spleen. They can also develop at the pancreatic tail, with similar characteristics regarding age, image findings, and elevated serum tumor markers (8)(9)(10). We herein describe a patient with a large splenic cyst, which was difficult to differentiate from a cyst of pancreatic origin, who was followed up for 6 years.…”
Section: Introductionmentioning
confidence: 92%
“…Thirdly, a derivation from the pancreatic duct may protrude into the accessory spleen (10). In a case described by Kadota et al (23), there were pancreatic ducts in the fibrous tissue surrounding the accessory spleen tissue, and the squamous and cuboidal epithelia indicated a transitional appearance from one form to the other. Additionally, immunohistochemical analysis demonstrated that the staining results of the cystic epithelial lining were identical to those of the pancreatic duct.…”
Section: Discussionmentioning
confidence: 93%
“…The histogenesis of an epidermoid cyst in an IPAS may be identical to that of a splenic epidermoid cyst (23). There are three hypotheses concerning the histogenesis of an epidermoid cyst in an IPAS (10).…”
Section: Discussionmentioning
confidence: 99%